1996
DOI: 10.1063/1.1147565
|View full text |Cite
|
Sign up to set email alerts
|

Study of forward characteristics of a cryogenic temperature sensor diode

Abstract: Simultaneous measurement of external refractive index and temperature based on long-period-grating-inscribed Sagnac interferometer and fiber Bragg grating Rev. Sci. Instrum. 83, 105001 (2012) Probing anisotropic heat transport using time-domain thermoreflectance with offset laser spots Rev. Sci. Instrum. 83, 104901 (2012) Spherical-sapphire-based whispering gallery mode resonator thermometer Rev. Sci. Instrum. 83, 094903 (2012) Evaluation of rare earth doped silica sub-micrometric spheres as optically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Schottky barrier diodes (SBDs) are generally used for designing sensors for temperature, pressure and atmospheric gas composition [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A SBD is also called a * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Schottky barrier diodes (SBDs) are generally used for designing sensors for temperature, pressure and atmospheric gas composition [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A SBD is also called a * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Among the commercially available technologies for sensing harsh environment temperature, silicon carbide (SiC) based devices were found to be an excellent candidate. 12 Therefore, this paper addresses the thermal sensitivity behavior of a temperature sensor based on state-of-art material, i.e., SiC, with small size. The most common temperature sensors among all commercially available sensors, which are being used in harsh environments, are optical sensors, thermocouples, resistive temperature detectors, thermistors, and semiconductor temperature sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature dependence of the current-voltage characteristics of a semiconductor p-n junction have been utilized in temperature measurement since last few decades. [1][2][3][4][5][6] It has been observed that the forward voltage drop across a p-n junction at constant current varies almost linearly with temperature. The slope of temperature-voltage curve depends on the value of forward current and it decreases towards higher currents.…”
Section: Introductionmentioning
confidence: 99%